2015
DOI: 10.1177/183335831504400102
|View full text |Cite
|
Sign up to set email alerts
|

Patient Innovation: An Analysis of Patients' Designs of Digital Technology Support for Everyday Living with Diabetes

Abstract: The aim of this paper is to identify characteristics of patients' contributions to innovation in health information technology (HIT). The paper outlines a theoretical definition of patient innovation and presents an analysis of four digital prototypes and 22 low-fidelity mock-ups designed by people affected by the chronic illness diabetes mellitus. Seventeen families (a total of 60 people) with one or more diabetic family members participated in design activities in a four-year research project focused on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 24 publications
(26 reference statements)
0
35
0
Order By: Relevance
“…In another study, Wherton and colleagues 37 conducted participatory design workshops with users of telehealth and telecare, their carers, service providers and technology suppliers. Another study 38 involved people with diabetes and their families in co-creating ideas and prototypes for digital technologies to support everyday living with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Wherton and colleagues 37 conducted participatory design workshops with users of telehealth and telecare, their carers, service providers and technology suppliers. Another study 38 involved people with diabetes and their families in co-creating ideas and prototypes for digital technologies to support everyday living with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Valuable mutual learning emerged between the participants throughout the development process. The significance of user involvement is emphasised by Kanstrup et al, 32 who found that, as key actors, patients can provide original designs that combine everyday living with medical technology in a way designers could not have done by themselves. This was similar in our study; the features and the content of the app and the workflow were developed in cooperation with patients and HCPs, which has been important for the usability in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The first working group (consisting of the patients, two researchers, and a facilitator) sought to collect insight into the user’s needs and system requirements. Brainstorming, paper prototypes, drawing an idea, graphical user interface (GUI) design, 41,42 and guided discussion methods regarding the technical restrictions were all used in order to illuminate the patients’ needs (see Table 1).…”
Section: Methodsmentioning
confidence: 99%